Copolymerization of palm oil with sulfur using inverse vulcanization to boost the palm oil industry. Issue 9 (November 2021) - Abbasi, Amin; Yahya, Wan Zaireen Nisa; Nasef, Mohamed Mahmoud; Moniruzzaman, Muhammad; Ghumman, Ali Shaan Manzoor
Nowadays, most of the world's palm oil is being produced in Malaysia and Indonesia; however, the demand for this vegetable oil as an edible oil is declining in many countries since consuming palm oil in excess can result in serious health problems. Consequently, finding new applications such as the production of bio-based polymers to make use of this cheap and abundant vegetable oil seems necessary. Herein, we report the copolymerization of palm oil with sulfur with different feed ratios via inverse vulcanization. The copolymers are then characterized using Fourier-transform infrared spectroscopy, differential scanning calorimetry and X-ray diffraction analysis. The results confirmed the formation of the polymers and their stability against depolymerization. Altogether, the obtained sulfur-palm oil copolymers showed great properties such as thermal stability up to 230°C under a nitrogen atmosphere and rubbery properties at room temperature. Although the Thermogravimetric analysis (TGA) thermograms had previously confirmed the high conversion of elemental sulfur into the polymeric structure by comparing the initial sulfur content and the final polysulfide content in the polymer, some unreacted elemental sulfur was also observed in the final product. Sulfur-palm oil (S-Palm oil) is a new green polymer that helps to find a new use for palm oil as a big industry as well as sulfur which is underutilized and left in stockpile as a byproduct in gas and petroleum refineries.